AB0847 HIGH TOLERABILITY OF USTEKINUMAB IN THE TREATMENT OF PATIENTS WITH ACTIVE PSORIATIC ARTHRITIS – RESULTS OF THE NON-INTERVENTIONAL STUDY SUSTAIN. (2nd June 2020) - Wendler, J.; Sieburg, M.; Movshovich, E.; Damann, N.; Behrens, F.
Abstract : Background: Several biologics available for the treatment of psoriatic arthritis (PsA) have demonstrated effectiveness. A major aim of the treating physician is to find the safest treatment for his patients. Objectives: In this work we analyzed the safety of ustekinumab in the treatment of PsA in a real-world setting. Methods: The SUSTAIN study is a prospective, multi-center non-interventional study in Germany designed to evaluate long term effectiveness and safety, quality of life, and other patient reported outcomes in patients with active PsA under treatment with ustekinumab in routine clinical care over the course of 160 weeks. Treatment with ustekinumab is according to the label recommendations. In the third interim analysis we evaluated the data of 336 included patients till week 112. Safety was evaluated based on the following parameters: numbers of adverse events (AEs), serious AEs (SAEs), and physicians' / patients' assessment of tolerability of treatment with ustekinumab. AEs are either reported by the subject voluntarily or are obtained by means of subject interviews at study visits. AE definitions, attribution rules, and severity criteria were pre-specified in the study plan. All AEs / SAEs were recorded and described including information on date of onset, seriousness, severity, outcome, action taken, and relationship to treatment as evaluated by the physician. All AEs were followed to satisfactory resolution or a clinically stable endpoint. Results: For this analysis 336 patients (57% women) at 75 centers were included. Data for key study visits were obtained for the following numbers of patients: 310 patients at week 4, 237 patients at week 40, 160 patients at week 76, and 108 patients at week 112. A total of 88 SAEs (9.0% of all reported AEs) have been documented through the data cut-off date including SAEs of the categories musculoskeletal and connective tissue disorders (n=21, 6.3% of all reported AEs), nervous system disorders (n=8, 2.4%), infections and infestations (n=9, 2.7%), neoplasms (n=4, 1.2%), cardiac disorders (n= 7, 2.1%). Overall, 14 (1.4% of all reported AEs) of the 88 SAEs were assessed as related to ustekinumab (Table 1 ). AEs and SAEs lead to permanent discontinuation of treatment with ustekinumab in 119 and 11 patients, respectively. The vast majority of AEs leading to treatment discontinuation amount to ineffective drug or drug effect decrease (n=84) and psoriatic arthropathy (n=16). The most frequent SAE leading to discontinuation was psoriatic arthropathy (n=4). Tolerability of therapy with ustekinumab was assessed as "very good" or "good" by 98.1% of the treating physicians after 76 weeks and by 100% after 112 weeks (Figure 1 A). Tolerability was assessed as "very good" or "good" by 98.7% of patients at week 76 and by 100% at week 112 (Figure 1 B). Overall, the safety profile of ustekinumab in this population of psoriatic arthritis patients through week 112 was generally consistent with that demonstrated in earlier studies. Conclusion: In this interim analysis of safety data from the non-interventional SUSTAIN study, ustekinumab was highly tolerated in the treatment of patients with active PsA in routine clinical practice through up to 112 weeks. Disclosure of Interests: Joerg Wendler Consultant of: Janssen, AbbVie, Sanofi, Speakers bureau: Roche, Chugai, Janssen, AbbVie, Novartis, Maren Sieburg: None declared, Evgenia Movshovich: None declared, Nils Damann: None declared, Frank Behrens Grant/research support from: Pfizer, Janssen, Chugai, Celgene, Lilly and Roche, Consultant of: Pfizer, AbbVie, Sanofi, Lilly, Novartis, Genzyme, Boehringer, Janssen, MSD, Celgene, Roche and Chugai